Profile Based Web Search Using Rule Ontology (International Journal of Scientific Research and Management (IJSRM), 2014)
: Web search engines help users find useful information on the World Wide Web (WWW). However, when the same query is submitted by different users, typical search engines return the same result regardless of who submitted the query. Generally, each user has different information needs for his/her query. Therefore, the search results should be adapted to users with different information needs. In this paper, we first propose a user profile based web search using rule acquisition through ontology. Rule is build based on user profile details, then the search result from engine is parsed based on this rule. Rule acquisition procedure using rule ontology RuleToOnto has been applied on the search result. The rule acquisition procedure consists of the rule component identification step and the rule composition step. And result is parsed and performed semantic matching and displayed to user according to the rule build up on user requirement. Only the information related to user profile will get displayed to the user and all other search results will be truncated